Revisiting subspecies identification of Common Kestrels (Falco tinnunculus): A critical look at Zhang et al. (2008) - Seong, Jin-Woo; Park, Jong-Gil; Nam, Dong-Ha (Zootaxa, 2025)
Zhang et al. (2008) investigated subspecific variation of Common Kestrels (Falco tinnunculus) wintering in Beijing, China, using a partial mtDNA control region (394–395bp), and concluded that two subspecies were present. However, analysis of their raw data revealed mostly double peaks at each nucleotide position, indicating ambiguity in the DNA sequence. These likely arose from a combination of factors, including irregular PCR efficiencies and slight primer mismatches. Zhang et al. (2008) likely misinterpreted these double peaks as evidence of distinct subspecies. This resulted in an inflated number (56) of variation sites. Their interpretation was further confounded by potential issues with their primers, designed from a sequence of F. peregrinus with a one-nucleotide difference. To address these limitations, we sequenced the full mtDNA control region (1,266bp) of 38 Common Kestrel samples using newly designed primers. This analysis yielded clean, single-peak profiles for each sequence, confirming that all samples belonged to F. t. interstinctus. We therefore propose reclassifying these populations as a single subspecies, F. t. interstinctus. Erroneous barcode sequences can distort subspecific identification and population structure, leading to inaccurate data and misleading phylogenetic inferences. Our study underscores the critical need for robust methods to minimize barcode sequencing errors. This would not only ensure accurate phylogenetic inferences for Common Kestrels but also support reliable population genetic studies across diverse taxa.